2010
DOI: 10.1007/s10464-009-9284-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Social Capital on the Depression of Urban Chinese Adolescents: An Integrative Framework

Abstract: Using data from an ongoing longitudinal study of 5,164 adolescents and their parents from seven cities in mainland China, this study investigated how social capital embedded in the family and the community, together with family human capital and financial capital, influenced the depressive symptoms of urban Chinese adolescents within an integrative framework. The structural equation modeling results suggested that higher community social capital was associated with lower level of adolescent depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 74 publications
2
46
0
Order By: Relevance
“…The sum scores of these two scales were used as observed indicators to form the latent construct of family social capital. These measures have been used in previous studies in the Chinese context with their validity and reliability established (Wu et al, 2010b(Wu et al, , 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The sum scores of these two scales were used as observed indicators to form the latent construct of family social capital. These measures have been used in previous studies in the Chinese context with their validity and reliability established (Wu et al, 2010b(Wu et al, , 2011.…”
Section: Methodsmentioning
confidence: 99%
“…A large body of literature has demonstrated the significant role of social capital in the development of children and adolescents, including psychosocial adjustment (Coleman, 1988(Coleman, , 1990Dorsey & Forehand, 2003;Morrow, 1999;Portes, 1998;Zhou & Bankston, 1994). Recent studies incorporate social capital embedded in various social contexts (e.g., family, school, neighborhood) into one integrative framework in order to examine and distinguish the effects of each dimension operating simultaneously (Wu et al, 2010). However, the conditional nature of these effects has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…As with North American and European populations (Avenevoli, Knight, Kessler & Merikangas, 2008), adolescence marks a critical period with regard to the development of depression in mainland China (Wu et al, 2010). Recent research conducted with adolescents (ages 13–22) in Shandong Province reported that 16.9% of youth reported severe symptoms of depression (Liu, Ma, Kurita & Tang, 1999), while other research conducted with adolescents (ages 13–16) in the Zhejiang Province reported that 33% of youth exhibited a history of severe depressive symptoms (Hesketh, Ding, & Jenkins, 2002).…”
mentioning
confidence: 99%